Challenges in Supervising VAT Collection within Electronic Commerce Systems - Siregar, Fakhri Jamal Yusuf; Nuryanah, Siti (E-Jurnal Akuntansi; Vol 35 No 2 (2025)DO - 10.24843/EJA.2025.v35.i02.p03, 2024)
The Directorate General of Taxes (DGT) has redefined the duties and functions of the Permanent Establishments and Expatriates Tax Office (KPP Badora) to include the supervision of business actors engaged in Trading Through Electronic Systems (TTES). This study aims to analyze the challenges faced by Account Representatives (ARs) at KPP Badora in supervising TTES VAT collectors, using the ADKAR model as an analytical framework. A case study approach was adopted, employing a mixed-methods research design. Data were collected through questionnaires and interviews to provide both quantitative and qualitative insights. The findings indicate that ARs encounter significant obstacles in supervising TTES VAT collectors, particularly in three aspects of the ADKAR model: knowledge, ability, and reinforcement. While awareness and desire were not identified as major challenges, the study highlights key difficulties in other areas. In the knowledge aspect, ARs lack a comprehensive understanding of the business processes of TTES VAT collectors. In the ability aspect, several challenges were identified, including the absence of comparative transaction value and traffic volume data, insufficient support from supervisory information systems, and unenforceable sanctions. Finally, in the reinforcement aspect, ARs lack a supervisory business process tailored to the unique characteristics of TTES VAT collectors, further complicating enforcement and compliance monitoring. Keywords: Account Representative; ADKAR; Supervision; VAT; TTES.